2016
DOI: 10.1186/s40665-016-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Root phenology in an Arctic shrub-graminoid community: the effects of long-term warming and herbivore exclusion

Abstract: Background: Shifts in phenology have been widely reported in response to global warming and have strong effects on ecosystem processes and greenhouse gas emissions. It is well documented that warming generally advances many phenophases of aboveground plant phenology, but its influence on root phenology is unclear. Most terrestrial biosphere models assume that root and shoot growth occur at the same time and are influenced by warming in the same manner, but recent studies suggest that this may not be the case. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
3
16
1
Order By: Relevance
“…Accordingly, as stress level, availability of light, water, and heat, and other factors vary along elevational gradients (Körner 2003), it is not surprising that the plant communities change in their functional composition along the elevation gradient in a predictable and concerted manner, too. It has been shown that traits of different plant organs respond heterogeneously to environmental changes (Radville et al 2016;Runquist et al 2016). Following this finding, the large within and relatively low between community variation in floral traits 1 3 suggest that these traits respond to different factors than vegetative traits.…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, as stress level, availability of light, water, and heat, and other factors vary along elevational gradients (Körner 2003), it is not surprising that the plant communities change in their functional composition along the elevation gradient in a predictable and concerted manner, too. It has been shown that traits of different plant organs respond heterogeneously to environmental changes (Radville et al 2016;Runquist et al 2016). Following this finding, the large within and relatively low between community variation in floral traits 1 3 suggest that these traits respond to different factors than vegetative traits.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, we can infer that almost all aboveground net primary productivity in Salix occurs early in the growing season. Radville et al (2016) also documented early season peaks in belowground productivity of tundra communities near Kangerlussuaq, Greenland, though phenology of deciduous shrub roots in particular were not reported.…”
Section: Positionmentioning
confidence: 96%
“…Permafrost thaw at 75 cm within the CiPEHR experiment took place in late August, long after aboveground 10.1029/2018JG004518 Journal of Geophysical Research: Biogeosciences plant structures had started to senesce (data not shown). Phenological studies in the Arctic, however, suggest belowground productivity extends well beyond that of aboveground structures (Blume-Werry et al, 2016;Radville et al, 2016). Uptake of N at the thaw front in late has been directly observed for deeply rooted species (Keuper et al, 2017) so DIN released directly from permafrost cannot be considered temporally inaccessible to plants.…”
Section: Locating the Release Of Din In Space And Timementioning
confidence: 99%